Maintaining Priority Customers by Implementing Customer Relationship Management (CRM): A Case Study at Emerald Banking BNI PTB (Perguruan Tinggi Bandung) - Pitaloka, Indira Diah; Pramadya, Hendri; Hendriyani, Chandra (Fakultas Pendidikan Ekonomi dan Bisnis, 2020)
AbstractThe focus of this research is to find out how the sales marketing find the new customers and CRO (Customer Relation Officer) Division maintain the existing customers with CRM program which include several media. This research was conducted at Bank BNI PTB Bandung for 300 hours practical work studies. This research is a descriptive research with qualitative approach in analyzing its data. The primary data were obtained from direct observation and interview with Bank BNI PTB Bandung employees and customers, while secondary data were obtained from books, documents from this company, internet, and research articles. From this research it is found out that the customers’ maintenance strategies at Bank BNI PTB Bandung have been run perfectly. The result of this research revealed that when the marketing strategies are implemented constantly to maintain a good relationship between the bank and the customers regarding the customers loyalty, it will have a positive impact for the bank in terms of customer relationship management. Keyword: Customer Relationship Management, Customers, Loyalty, Maintenance Strategy. AbstrakFokus dari penelitian ini adalah untuk mengetahui bagaimana pemasaran penjualan menemukan pelanggan baru dan Divisi CRO (Customer Relation Officer) mempertahankan pelanggan yang ada dengan program CRM yang mencakup beberapa media. Penelitian ini dilakukan di Bank BNI PTB Bandung selama 300 jam. Penelitian ini adalah penelitian deskriptif dengan pendekatan kualitatif dalam menganalisis datanya. Data primer diperoleh dari observasi langsung dan wawancara dengan karyawan dan pelanggan Bank BNI PTB Bandung, sedangkan data sekunder diperoleh dari buku, dokumen dari perusahaan ini, internet dan artikel penelitian. Dari penelitian ini peneliti menemukan bahwa strategi pemeliharaan di Bank BNI PTB Bandung telah berjalan dengan sempurna. Hasil penelitian ini telah berhasil menguak bahwa ketika strategi diterapkan secara konstan untuk menjaga hubungan antara bank dan nasabah terkait dengan loyalitas nasabah, itu akan berdampak positif bagi perusahaan khususnya dalam pengelolaan hubungan baik dengan nasabah/ pelanggan. Kata Kunci: Manajemen Hubungan Pelanggan, Pelanggan, Loyalitas, Strategi Pemeliharaan.